Factors associated with retention of nurse assistants in a hospital setting: A qualitative study. Issue 4 (April 2023) - Cottrell, Constance; Adlesic, Melanie; Albert, Nancy
Abstract : This study identified four main themes related to the retention of nurse assistants in a community hospital. A culture of respectful communication among team members can support retention.